Development of Integrated Science Learning Module of Religious Value to Develop Independent Characters For Students - Intan Rahma Utami; Retno Triwoelandari; M. Kholil Nawawi (IJER (Indonesian Journal of Educational Research), 2020)
In learning activities that are the main focus is recognizing the character of students to determine learning resources or teaching materials that will be used in the learning process so that the objectives of the learning can be achieved. But in reality, there are still many parties who are not aware of this. So that the teaching materials used have not been able to develop the character possessed by students fully. One of the ways to develop the character of students in school is to integrate character education and religious values into integrated learning. The purpose of this study is to determine the feasibility of the learning module that will be used by students. The study uses the Research and Development (R&D) 4D model. The results of the study showed that the numbers obtained from design experts were 70.45%, material experts 75%, and linguists 75%, and student assessment results were 86.11%. At the testing stages, the average posttest has increased by 7.20690. Thus, the integrated IPA learning module is worthy of religious values used to develop students' independent character based on their level of feasibility.